Analisis Peran Customer Service Dalam Pelayanan Produk Tabungan Haji Untuk Meningkatkan Kepuasan Nasabah di PT. Bank Syariah Indonesia Kantor Cabang Jember Sudirman - Az-Zahra Nuril Firdaus; Siti Nur Holisah; Ayu Sa’adah (Jurnal Ekonomi dan Bisnis Digital, 2023)
This study aims to determine the service of Hajj savings products at Bank Syariah Indonesia KC Jember Sudirman and find out customer satisfaction with the services of Indonesian Hajj savings products. In this study, the author used qualitative research methods with a descriptive approach. The results of this study show that Customer service at BSI KC Jember Sudirman in providing services, namely being friendly, speaking softly with intonation, politeness, courtesy, with a low voice so that customers can understand what is conveyed and several strategies, namely 1. Serving wholeheartedly and meeting customer expectations so that customers become loyal 2. Offer quality products 3. Submit data and information accurately and correctly 4. Prioritizing the interests of the company above personal interests and work units. The roles carried out to increase customer satisfaction with Hajj savings products at BSI KC Jember Sudirman are 1. Using quality products so that customers will feel satisfied 2. Providing excellent service so that customers feel comfortable and according to the desired expectations 3. Providing empathy for customers so that customers have confidence, a sense of pride in the products used and have high confidence in the products provided at BSI KC Jember Sudirman.